2002
DOI: 10.1182/blood.v99.12.4336
|View full text |Cite
|
Sign up to set email alerts
|

Ibritumomab tiuxetan radioimmunotherapy for patients with relapsed or refractory non-Hodgkin lymphoma and mild thrombocytopenia: a phase II multicenter trial

Abstract: , 1-9). Estimated radiation-absorbed doses were well below the study-defined maximum allowable for all 30 patients. With the use of the International Workshop criteria for NHL response assessment, the overall response rate was 83% (37% complete response, 6.7% complete response unconfirmed, and 40% partial response). Kaplan-Meier estimated median time to progression (TTP) was 9.4 months (range, 1.7-24.6). In responders, Kaplan-Meier estimated median TTP was 12.6 months (range, 4.9-24.6), with 35% of data censor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
92
2
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(102 citation statements)
references
References 33 publications
(24 reference statements)
5
92
2
3
Order By: Relevance
“…In patients who achieved CR/CRu TTP was 24.7 months for RIT and 13.2 months for rituximab alone (Gordon et al, 2004b). Other phase II trials with 90 Y-ibritumomab tiuxetan reported CR/Cru rates between 15 and 51% (Wiseman et al, 2002;Witzig et al, 2002a;Gordon et al, 2004a) the follow-up being frequently shorter compared with the present study or that of Davies (Davies et al, 2004). Therefore, it is clear that both agents have demonstrated high levels of efficacy in patients with relapsed/refractory disease.…”
Section: Toxicitycontrasting
confidence: 47%
“…In patients who achieved CR/CRu TTP was 24.7 months for RIT and 13.2 months for rituximab alone (Gordon et al, 2004b). Other phase II trials with 90 Y-ibritumomab tiuxetan reported CR/Cru rates between 15 and 51% (Wiseman et al, 2002;Witzig et al, 2002a;Gordon et al, 2004a) the follow-up being frequently shorter compared with the present study or that of Davies (Davies et al, 2004). Therefore, it is clear that both agents have demonstrated high levels of efficacy in patients with relapsed/refractory disease.…”
Section: Toxicitycontrasting
confidence: 47%
“…Once bound to their respective target, Mab's induce antitumour activity by one of three principle mechanisms: antibody-dependent cell-mediated cytotoxicity (Clynes et al, 2000), interruption of aberrant cell-signalling proteins (Le et al, 2000) or delivery of a cytotoxic moiety such as a drug, radioisotope or toxin to the tumour (Wiseman et al, 2002). Antibody therapy does, however, have a number of limitations such as poor penetration into tumour, selection of apoptosis-resistant tumour clones and inactivation of Mab by serum proteins (Reilly et al, 1995;Jain, 1999).…”
mentioning
confidence: 99%
“…1 Conventional treatment options for FL patients include multiagent chemotherapy combined with anti-CD20 monoclonal Abs 2,3 or radioimmunotherapy, 4,5 leading to an improvement of median overall survival (OS) of 12-14 years in the last decade. 6 High-dose salvage regimens, including chemotherapy, rituximab and/or TBI, followed by autologous hematopoietic cell transplantation (HCT) have also clearly improved 5-year PFS and OS.…”
Section: Introductionmentioning
confidence: 99%